Nilai Moral dalam Novel Hati Suhita Karya Khilma Anis - Arsad, Arsad; Yusnan, Muhammad (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2020)
The study of this novel uses a literary sociology approach that takes into account the importance or interrelationship between literature and society. The method used in this research is descriptive qualitative method, which means describing words, phrases, sentences and paragraphs contained in the novel. This research is a type of library research because the source of the research is from Novels. The data collection technique used in this study is the reading and note taking technique. From the analysis of the data obtained in this study, it can be concluded that the moral values ​​contained in the novel Hati Suhita by Khilma Anis include: a. moral values ​​related to God include being grateful, surrendering, praying, praising the majesty of God, b. Moral values ​​related to oneself include patience, self-confidence, steadfastness in maintaining marwa, never giving up (tough), admitting mistakes, c. Human relations with other humans in the social sphere include parental love for children, affection for friends/relatives, advice between friends/relatives, help, children's affection for parents, courtesy, respect and gratitude.